Influence of form defect on the mechanical behavior and stress intensity factor of shrink-fitted thick-walled cylinders - Boutoutaou, Hamid; Chebbab, Brahim; Belmessous, Abdelmounaime (Zielona Góra: Uniwersytet Zielonogórski)
In this research work, the finite element software, ABAQUS is used to study by simulations the influence of form defect on mechanical behavior of a shrink-fitted assembly presenting internal radial cracks. Under the action of contact pressure induced by the tightening between two cylinders, these cracks resulting from incorrect assembly operations or materials elaboration defect, can be harmful to the assembly.
Keywords: shrink-fit; thick-walled cylinder; finite elements; stress intensity factor; crack cylinder